2019
DOI: 10.3389/fmed.2019.00229
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Pneumonic Tularemia in Operation Whitecoat Human Subjects: Disease Progression and Tetracycline Efficacy

Abstract: Francisella tularensis is a highly infectious Gram-negative bacterium that is the etiologic agent of tularemia in animals and humans. The incidence of tularemia is very low with a lack of comprehensive data that describe disease in humans due to difficulty in understanding time and routes of exposure. Under the title Operation Whitecoat, researchers at Ft. Detrick, MD conducted 40 clinical studies of tularemia from 1958 to 1968. In these studies, one of the objectives was to evaluate candidate countermeasures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Currently, only LVS has been shown to protect humans against inhalation of virulent Ftt. This data stems solely from experiments conducted between 1960-1975 in which volunteers or tularemia researchers immunized by various routes with LVS were subsequently exposed to SCHU S4 [16][17][18]21,52,53]. These studies showed that LVS administered by scarification provided the simplest and safest means of eliciting protection, though it proved sub-optimal against aerosol challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only LVS has been shown to protect humans against inhalation of virulent Ftt. This data stems solely from experiments conducted between 1960-1975 in which volunteers or tularemia researchers immunized by various routes with LVS were subsequently exposed to SCHU S4 [16][17][18]21,52,53]. These studies showed that LVS administered by scarification provided the simplest and safest means of eliciting protection, though it proved sub-optimal against aerosol challenge.…”
Section: Discussionmentioning
confidence: 99%
“…challenge experiments on healthy volunteers, participants in 'Operation White Coat', exposed to various doses over 10 years starting in 1958 (10). There is a clear infectious dose-response relationship with reduced time of onset and more severe disease occurring at higher exposures.…”
Section: Introductionmentioning
confidence: 99%
“…There is a clear infectious dose-response relationship with reduced time of onset and more severe disease occurring at higher exposures. Aerosolized tularemia may relapse if not treated with 10-14 days of sufficient antibiotic therapy equivalent to > 2 grams per day tetracycline (10). Though tetracycline itself is no longer recommended, doxycycline continues to be a treatment option as well as fluoroquinolones and aminoglycosides (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LVS represents the most advanced tularemia vaccine candidate in western countries but is still investigational in the U.S. Remarkably, human challenge studies that exposed naive and LVS-vaccinated people to virulent Type A tularemia were performed in the 1960’s, during military-sponsored studies known as Operation Whitecoat 5 . These studies suggested LVS can provide partial protection in an experimental setting 6 8 , but its efficacy has not been evaluated in field trials.…”
Section: Introductionmentioning
confidence: 99%